Assessment of Mobile Phone Usage and Loneliness Levels of Faculty of Sports Sciences Students - Sezer, Süreyya Yonca; Şenbakar, Kubilay (Tamer KUTLUCA, 2023)
With the introduction of the mobile phone into our life, several social media and game applications were created, and individuals began to spend their time in the virtual world. The purpose of this study was to measure the loneliness levels of students at the Faculty of Sport Sciences using mobile phones. People have been more focused on their mobile phones as technology has advanced, and this has unavoidably led to a shift away from the environment and people. The research population consists of students from Fırat University’s Faculty of Sports Sciences. The sample consists of 146 students enrolled in the faculty of sports sciences in the academic year 2022-2023. The “Problematic mobile phone use scale” established by Kutlu and Pamuk and the “UCLA loneliness scale” developed by Russell (1996) were utilized as data collection techniques in the study. The SPSS package program was used to analyze the data. Female students of the Faculty of Sports Sciences had higher mobile phone usage values than male students, and their loneliness levels were lower than male students, according to our study, and when the values of the students participating in the study were examined, they used mobile phones between 0-4 hours. As a result, in our study, it was shown that students generally spend the majority of their time alone on the phone and playing games, while female students’ PCPU (Problematic Mobile Phone Use Scale) scores are higher than men’s, and women’s values on the UCLA loneliness scale are low.

With the introduction of the mobile phone into our life, several social media and game applications were created, and individuals began to spend their time in the virtual world. The purpose of this study was to measure the loneliness levels of students at the Faculty of Sport Sciences using mobile phones. People have been more focused on their mobile phones as technology has advanced, and this has unavoidably led to a shift away from the environment and people. The research population consists of students from Fırat University’s Faculty of Sports Sciences. The sample consists of 146 students enrolled in the faculty of sports sciences in the academic year 2022-2023. The “Problematic mobile phone use scale” established by Kutlu and Pamuk and the “UCLA loneliness scale” developed by Russell (1996) were utilized as data collection techniques in the study. The SPSS package program was used to analyze the data. Female students of the Faculty of Sports Sciences had higher mobile phone usage values than male students, and their loneliness levels were lower than male students, according to our study, and when the values of the students participating in the study were examined, they used mobile phones between 0-4 hours. As a result, in our study, it was shown that students generally spend the majority of their time alone on the phone and playing games, while female students’ PCPU (Problematic Mobile Phone Use Scale) scores are higher than men’s, and women’s values on the UCLA loneliness scale are low.
Assessment of Mobile Phone Usage and Loneliness Levels of Faculty of Sports Sciences Students
Keywords: Development of Physical Education and Education Programs; Beden Eğitimi ve Eğitim Programlarının Geliştirilmesi